Analysis of the Impact of House Prices and Income on Purchasing Decisions of Millennials and Generation Z in Bekasi Regency - Windi, Windi; Ghofar, Ida Abdul; Mahribi, Muhamad Dwiki Noval (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study examines the influence of price and income on home purchase decisions in Bekasi Regency, framed within the context of Indonesia’s improving housing conditions. National data show a reduction in the housing backlog from 16.14 million units in 2022 to 14.84 million units in 2023, reflecting notable progress in meeting residential needs. The population under investigation consists of millennials and Generation Z in Bekasi Regency, who are increasingly influential demographic groups in the housing market. Using non-probability sampling techniques, this study involved 100 respondents to collect relevant data. A quantitative approach utilizing SEM-PLS analysis was employed to evaluate the proposed hypotheses. The research findings show that house price significantly influences purchasing decisions with a p-value 0.05. The results of the coefficient of determination (R²) analysis indicate that the purchase decision variable has an R² value of 0.473, suggesting that 47.3% of its variance is explained by the factors of housing price and income, while the remaining 52.7% is influenced by other external variables. These findings emphasize that, although income affects purchasing power, price remains the primary determinant of home-buying decisions. The study provides guidance for developing more effective housing marketing strategies and serves as a reference for future research on other influencing factors in the property market.